Palmitic Acid, but Not Lauric Acid, Induces Metabolic Inflammation, Mitochondrial Fragmentation, and a Drop in Mitochondrial Membrane Potential in Human Primary Myotubes - Sergi, Domenico; Luscombe-Marsh, Natalie; Naumovski, Nenad; Abeywardena, Mahinda; O'Callaghan, Nathan (Frontiers in Nutrition, 2021)
The chain-length of saturated fatty acids may dictate their impact on inflammation and mitochondrial dysfunction, two pivotal players in the pathogenesis of insulin resistance. However, these paradigms have only been investigated in animal models and cell line so far. Thus, the aim of this study was to compare the effect of palmitic (PA) (16:0) and lauric (LA) (12:0) acid on human primary myotubes mitochondrial health and metabolic inflammation. Human primary myotubes were challenged with either PA or LA (500µM). After 24 hours, the expression of interleukin-6 (IL-6) was assessed by qPCR, whereas Western blot was used to quantify the abundancy of the inhibitor of nuclear factor kappa-B (IKBα), electron transport chain complex proteins and mitofusin-2 (MFN-2). Mitochondrial membrane potential and dynamics were evaluated using tetraethylbenzimidazolylcarbocyanine iodide (JC-1) and immunocytochemistry, respectively. PA, contrarily to LA, triggered an inflammatory response marked by the upregulation of IL-6 mRNA (11- fold; P<0.01) and a decrease in IKBα (32%; P<0.05). Furthermore, while PA and LA did not differently modulate the levels of mitochondrial electron transport chain complex proteins, PA induced mitochondrial fragmentation (37%; P<0.001), decreased MFN-2 (38%; P<0.05) and caused a drop in mitochondrial membrane potential (11%; P<0.01) compared to control, with this effect being absent in LA-treated cells. Thus, LA, as opposed to PA, did not trigger pathogenetic mechanisms proposed to be linked with insulin resistance and therefore represents a healthier saturated fatty acid choice to potentially preserve skeletal muscle metabolic health.